Jaket Serat Sabut Kelapa: Inovasi Penggunaan Limbah Alami Untuk Produk Tekstil Fungsional - Pratiwi, Citra Sukma; Wulan Saftihatini Atikah (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Coconut husk is a fibrous part of the coconut fruit that is commonly processed into crafts and new materials. It contains 63.38% fiber, primarily composed of cellulose. With technological advancements, coconut husk fibers are increasingly used in industries such as carpets, cushions, mattresses, and pillows. This study aims to utilize coconut husk fibers as a raw material for textiles and garments, specifically as a jacket filler. The insulating properties of coconut husk make it a potential alternative for jacket padding. The fiber has a circular cross-sectional shape with large cavities, allowing for significant air absorption. To improve the quality of the coconut husk fibers, chemical treatments such as scouring and softening were applied. The jacket developed in this study is a puffer jacket, with coconut husk fibers as the filler and viseline fabric used to bind the fibers. The stitch-through construction method was employed to keep the fibers in place. Experimental evaluation showed that the coconut husk jacket performs similarly in temperature insulation compared to jackets filled with goose down and synthetic materials. Additional testing confirmed that the main fabric of the jacket exhibits water-repellent properties, aligning with the standards of a typical puffer jacket.